Long-term follow-up of deep anterior lamellar keratoplasty after Descemet stripping automated endothelial keratoplasty - Fuest, Matthias (2020)
Aims: To describe the long-term outcomes of deep anterior lamellar keratoplasty (DALK) performed after Descemet stripping automated endothelial keratoplasty (DSAEK) in cases of infection and residual stromal opacity. Methods: Ten eyes of nine consecutive patients undergoing DALK after DSAEK at a single tertiary referral center (SNEC) from 2011 to 2016 were analyzed for best spectacle-corrected visual acuity (BSCVA), refraction, spherical equivalent (SE) and cylinder, as well as graft diameters, survival, and complications. Results: The mean pre-DSAEK BSCVA was 1.73 ± 0.76 LogMAR. At a mean follow-up of 9.8 ± 7.1 months, visual acuity had improved significantly (p = 0.028) to 1.09 ± 0.55 LogMAR after DSAEK. DALK was performed at 10.3 ± 7.2 months after DSAEK because of residual stromal scarring in nine and a corneal infection in one case. At the last follow-up visit (19.4 ± 13.9 months) after DALK, BSCVA had improved to 0.38 ± 0.6 LogMAR, significantly better than after DSAEK alone (p = 0.015) and before DSAEK (p = 0.018). Spherical equivalent (− 4.8 ± 3.5 D) and cylinder (− 2.5 ± 2.0 D) did not show significant changes compared to after DSAEK (SE p = 0.17; cylinder p = 0.19) or 3 months after DALK (SE p = 0.17; cylinder p = 0.46). One endothelial graft failed 3 months after DALK. Kaplan-Meier estimated average survival for all cases was 45.3 (95% CI 36.6–54.0) months. The cumulative survival probability for the entire cohort was 90% at 1, 2, and 4 years of follow-up. Conclusions: DALK surgery after DSAEK can improve vision in cases of residual host scarring and treat host corneal infection, while avoiding open-sky surgery and sparing a healthy endothelial graft.